Charge transfer of carbon nanomaterials for efficient metal‐free electrocatalysis. Issue 1 (31st January 2022) - Paul, Rajib; Zhai, Qingfeng; Roy, Ajit K.; Dai, Liming
Abstract: Recently, carbon‐based metal‐free electrocatalysts (C‐MFECs) have drawn considerable research attention because of their attractive physicochemical characteristics, cost‐effectiveness, and ability to convert and store energy efficiently. Efficient intramolecular charge transfer among different parts of the carbon electrocatalyst and/or intermolecular charge transfer between electrocatalyst and electrolyte dictate the ultimate energy conversion performance. Experimental results and theoretical analyses have demonstrated that rational design of metal‐free carbon nanomaterials, coupled with proper intramolecular charge transfer through heteroatom doping, incorporation of Stone–Wales defects, and/or intermolecular charge transfer through adsorption of appropriate molecules/moieties, can promote efficient electrocatalysis. In this article, we will first provide the related theoretical principles and then present an overview on the rational design and development of C‐MFECs for efficient charge transfer, followed by elucidating charge‐transfer processes for different electrocatalytic reactions related to renewable energy conversion and environmental remediation technologies. Finally, the current challenges and future perspectives in this exciting field will be discussed. Abstract : Intra‐/intermolecular charge transfer plays an important role in regulating the catalytic performance of carbon‐based metal‐free electrocatalysts (C‐MFECs). This article provides a systematic overview on the electrocatalytic activities of C‐MFECs induced by charge transfer associated with the heteroatom/defect doping and/or physicochemical adsorption, along with current challenges and future perspectives in this emerging field.